2018
DOI: 10.2174/1574888x13666180502100620
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells as Molecular Targets in Vascular Senescence and Repair

Abstract: Endothelial progenitor cells are circulating blood cells derived from various sources like bone marrow, spleen, umbilical cord, liver, kidney and other sources that play a vital role in the regeneration of the endothelial lining of blood vessels and wound repair. There are two types of EPCs, early EPCs and late EPCs. EPCs are believed to originate from hematopoietic stem cells and mesenchymal stem cells. The mobilization of progenitor cells from bone marrow to the peripheral circulation is highly regulated und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Persistent hyperglycemia results in physiologic dysfunction at all stages of the wound-healing process largely attributed to the overproduction of reactive oxygen species. Likewise, it is widely appreciated that deranged angiogenesis, insufficient recruitment of circulating EPCs, and dysfunctional endothelial cells (ECs) migration and proliferation all serve to impair tissue repair in diabetic patients [ 56 ]. A full network of capillary blood vessels is critical for the delivery of oxygen, nutrients, and growth factors that are required for effective wound healing [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent hyperglycemia results in physiologic dysfunction at all stages of the wound-healing process largely attributed to the overproduction of reactive oxygen species. Likewise, it is widely appreciated that deranged angiogenesis, insufficient recruitment of circulating EPCs, and dysfunctional endothelial cells (ECs) migration and proliferation all serve to impair tissue repair in diabetic patients [ 56 ]. A full network of capillary blood vessels is critical for the delivery of oxygen, nutrients, and growth factors that are required for effective wound healing [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mature ECs can proliferate and migrate to promote repair at sites of tissue damage [ 56 ]. Enhanced proliferative and migratory capacities of ECs will promote the ability to repair damaged blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPCs are not only derived from bone marrow, but also from spleen, vascular outer membrane, and even some endothelial cells themselves, moreover, they have different tendency to differentiate and repair tissues (Kamei et al, 2017;Rana et al, 2018). Even so, bone marrow-derived EPCs are still the main source of EPCs in the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs capturing biomolecules were immobilized onto metal-based biomaterial surfaces to accelerate reendothelialization [9]. Some researchers suggested that circulating EPCs can not only accelerate reendothelialization by paracrine but also differentiate into mature VECs [10]. Others claimed that EPCs never differentiate into mature VECs to cover the area of injury.…”
Section: Introductionmentioning
confidence: 99%